Pengaruh Kualitas Layanan Terhadap Kepuasan Nasabah Pada Produk BSI Tabungan Easy Wadiah - Sup, Devid Frastiawan Amir; Sabaruddin (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2024)
Banks in their development will always face very competitive situations. It is important for banks to be able to achieve competitive advantage, one thing banks can do is to develop service quality. Banks must do several things that can bind customers' hearts to remain loyal to the bank, so the services provided by the bank must be right on target, so that customer satisfaction becomes an important part of maintaining customer loyalty to the bank. This research aims to measure the influence of service quality on customer satisfaction with the BSI Easy Wadiah Savings product, at Bank Syariah Indonesia KCP Magelang Muntilan, Central Java. The method used in this research is a quantitative method, using SPSS software analysis tools. There are two variables used in this research, namely the independent variable Service Quality (X) and the dependent variable Customer Satisfaction (Y). The results obtained from this research are that there is a positive and significant influence between service quality and customer satisfaction. If service quality increases, customer satisfaction will also be higher. This is proven by the results of the t test analysis which shows the calculated t is 19.213 with a significance level of 0.01.